(untitled) (Research, Society and Development, 2021)
Objective: To identify in the scientific literature the factors that contribute to early weaning in Brazil. Methodology: Integrative review carried out at the Virtual Health Library, which allows simultaneous access to the electronic databases BDENF, IBECS and LILACS, through the following descriptors: breastfeeding, weaning, infant, lactating, infant care and child health. Results: 12 articles made up the final sample of this study, so that the most frequent factors associated with early weaning were pacifier use (n: 03), maternal education (n: 02), maternal belief in lack of milk (n: 02 ), working outside the home (n: 02), bottle feeding (n: 02), maternal smoking (n: 01), being primiparous (n: 01), economic class (n: 01) and marital status (n: 01). Conclusion: The factors associated with early weaning found in studies carried out in Brazil are related to life habits and belief, as well as to the socioeconomic characteristics of the mothers, which can cause damage to the health of both the infant and the infant.